Novel molecular targets for atrial fibrillation therapy - Dobrev, Dobromir; Carlsson, Leif; Nattel, Stanley (Nature reviews. Drug discovery, 2012)
Atrial fibrillation is the most common type of cardiac arrhythmia, and is responsible for substantial morbidity and mortality in the general population. Current treatments have moderate efficacy and considerable risks, especially of pro-arrhythmia, highlighting the need for new therapeutic strategies. In recent years, substantial efforts have been invested in developing novel treatments that target the underlying molecular determinants of atrial fibrillation, and several new compounds are under development. This Review focuses on the mechanistic rationale for the development of new anti-atrial fibrillation drugs, on the molecular and structural motifs that they target and on the results obtained so far in experimental and clinical studies.
Gesehen am 04.04.2018